2015
DOI: 10.5558/tfc2015-050
|View full text |Cite
|
Sign up to set email alerts
|

Ash regeneration capacity after emerald ash borer (EAB) outbreaks: Some early results

Abstract: The emerald ash borer (EAB), a wood-boring beetle native of Asia, has killed millions of ash trees in North America since its detection in 2002. The rapid spread of the infestation and the widespread distribution and importance of ash in North America, coupled with the genus' high vulnerability raise the crucial question of ash regeneration capacity following EAB infestation and its potentially broad ecological implications. We report on ash regeneration and infestation at the epicentre of the initial EAB inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 22 publications
3
13
0
Order By: Relevance
“…Although parasitoid prevalence in some ash trees is as high as 35% for O. agrili and >90% for T. planipennisi at some study sites, the mature ash trees still experienced high mortality as they were already dead or dying when parasitoid releases began [31,37]. In areas no treated with biocontrol, up to 19% of the stems in the regenerating sapling layer can also be infected [76]. However, younger, thin barked ash trees and saplings growing at these release sites seem to be protected by the dominant biocontrol agent T. planipennisi, a small parasitoid with a short ovipositor that successfully parasitizes EAB larvae in ash trees <10 cm DBH [37,40,77,78].…”
Section: Do Biocontrol Agents Affect Ash Sapling Density?mentioning
confidence: 91%
“…Although parasitoid prevalence in some ash trees is as high as 35% for O. agrili and >90% for T. planipennisi at some study sites, the mature ash trees still experienced high mortality as they were already dead or dying when parasitoid releases began [31,37]. In areas no treated with biocontrol, up to 19% of the stems in the regenerating sapling layer can also be infected [76]. However, younger, thin barked ash trees and saplings growing at these release sites seem to be protected by the dominant biocontrol agent T. planipennisi, a small parasitoid with a short ovipositor that successfully parasitizes EAB larvae in ash trees <10 cm DBH [37,40,77,78].…”
Section: Do Biocontrol Agents Affect Ash Sapling Density?mentioning
confidence: 91%
“…In addition, the 58% ash mortality documented by Kashian [33] would have generated larger canopy gaps than observed by Klooster et al [13], where ash was a significantly lower component of more diverse forest stands [14]. In southeastern Ontario, Aubin et al [35] also observed substantial ash regeneration from basal sprouting. However, inter-and intraspecific competition experienced by regenerating ash would have been limited there as well, because the amount of pre-EAB ash basal area in the sampled stands was greater than twice that of all other species combined, and more than 99% ash basal area died following EAB establishment [35].…”
Section: Ash Seed Bank Seedling Regeneration and Basal Sproutingmentioning
confidence: 89%
“…Epicormic basal sprouting can contribute to ash regeneration [34] and is a common response of ash trees that have had their canopies killed by EAB [33,35], especially for open-grown trees ( Figure 2). However, no such regeneration was observed by Klooster et al [13] in the closed-canopy mixed deciduous forests of the Upper Huron River watershed, where basal sprouts exhibited low vigor and died with the canopy or soon thereafter, perhaps due to strong interspecific competition for light and other resources in the understory of these diverse forests [14].…”
Section: Ash Seed Bank Seedling Regeneration and Basal Sproutingmentioning
confidence: 99%
“…Our field surveys showed that ash can be a common, sometimes dominant, riparian tree species and a significant contributor to leaf litter deposition in the agricultural landscape of southwestern Ontario where EAB infestations are burgeoning (Aubin et al 2015). Nisbet et al (2015) predicted that because ash is likely a high-quality food source for aquatic consumers based on its nutrient quality, the loss of ash litter from EAB infestations in riparian forests would have measurable consequences for litter consumers.…”
Section: R a F Tmentioning
confidence: 92%
“…Elm was relatively common in riparian plots of our study area (fourth most common riparian tree in terms of stem density) but is susceptible to Dutch elm disease which is still a serious threat to native North American elm (Knight et al 2012). However, the risk to litter consumers from the loss of elm trees is not as high as from the loss of ash trees because Dutch elm disease only affects matures trees and kills them relatively slowly whereas EAB rapidly kills even small ash saplings thereby virtually eliminating ash canopy trees (Aubin et al 2015). Nevertheless, the rapid loss of ash from EAB coupled with a slow loss of mature elm from Dutch elm disease where both species are present in riparian forests will undoubtedly exacerbate the reductions in high-quality food resources for consumers.…”
Section: R a F Tmentioning
confidence: 99%